Sosialisasi Pencegahan Bullying Kepada Kalangan Siswa SD di Desa Weleri - Asyif Faozi; Rina Ariyani; Ilham Dhiya Ul Haq Ramadhan (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
Bullying cases in Indonesia often occur in educational settings. In recent years, incidents of bullying among children in schools, ranging from elementary to college levels, have become more frequent. This phenomenon shows a decline in morality among children today. This socialization activity is carried out by observation, namely direct observation to the field (field research), where after that, preparation and planning are carried out and prepare materials for presentation as well as the use of film media as one of the learning media. Bullying is a form of abuse of power, with various forms such as verbal, physical, and social actions that aim to humiliate and hurt their victims. The consequences can be severe and long-lasting, affecting mental and emotional health. Bullying can be influenced by various conditions including physical, psychological, economic, social, cultural and gender differences